Contexts, beliefs and health behaviour: Are individuals who engage in risky sexual behaviour likely to wear facemasks against COVID-19? - Yemi Adewoyin; Chukwuedozie K. Ajaero; Clifford O. Odimegwu (AOSIS, 2022)
and availability of sanitation facilities, individual health beliefs and behaviour are critical in combating the sustained prevalence of Covid-19. Behaviour has, however, been shown to be consistent but could be context-dependent based on the individual's beliefs. To investigate whether or not individuals' protective behaviour against coronavirus is associated with their behaviour in a previous health context. Facemask usage and engagement in risky sexual behaviour (RSB) were employed as corollaries of Covid-19 protective behaviour and a previous health context respectively. Data on them and other sociodemographic correlates of health behaviour were collected on 522 Nigerians via a web-based survey. The data were analyzed using frequency, Chi Square and Binary Logistics Regression. About 31% of the population wore facemasks in public, 48.1% believed Covid existed and was severe, and 31.6% had engaged in RSB. Individuals who engaged in RSB had lower odds of wearing facemasks in public in both the general population and across the rural-urban divide. The relationship was, however, only statistically significant (OR:0.642, p0.05) in the adjusted regression model. Other significant determinants of facemask use were gender, place of residence, employment status and beliefs about Covid. The similarity of individual beliefs and behaviours in different health contexts provides an opportunity to model behaviour change communication policies for preventing and combating the spread of coronavirus and other infectious diseases.